A new methodological approach to characterize selective motor control in children with cerebral palsy - Graci, Valentina; O’Neill, Mitchel; Bloss, Meredith; Akkem, Rahul; Paremski, Athylia C.; Sanders, Ozell; Prosser, Laura A. (Frontiers in Human Neuroscience, 2024)
Despite being a primary impairment in individuals with cerebral palsy (CP), selective motor control (SMC) is not routinely measured. Personalized treatment approaches in CP will be unattainable without the ability to precisely characterize the types and degrees of impairments in motor control. The objective of this study is to report the development and feasibility of a new methodological approach measuring muscle activation patterns during single-joint tasks to characterize obligatory muscle co-activation patterns that may underly impaired SMC.Methods. Muscle activation patterns were recorded during sub-maximal voluntary isometric contraction (sub-MVIC) tasks at the hip, knee, and ankle with an interactive feedback game to standardize effort across participants. We calculated indices of co-activation, synergistic movement, mirror movement, and overflow (indices range 0-2, greater scores equal to greater impairment in SMC) for each isolated joint task in 15 children -8 with typical development (TD) (mean age 4.7 ± 1.0 SD years) and 7 with CP (mean age 5.8 ± 0.7 SD years). Indices were compared with Mann-Whitney tests. The relationships between the indices and gross motor function (GMFM-66) were examined with Pearson's r.Mean indices were higher in the CP vs the TD group for each of the six tasks, with mean differences ranging from 0.05 (abduction and plantarflexion) to 0.44 (dorsiflexion). There was great inter-subject variability in the CP group such that significant group differences were detected for knee flexion mirroring (p=0.029), dorsiflexion coactivation (p=0.021), and dorsiflexion overflow (p=0.014). Significant negative linear relations to gross motor function were found in all four indices for knee extension (r= -0.56 to -0.75), three of the indices for ankle dorsiflexion (r= -0.68 to -0.78) and in two of the indices for knee flexion (r= -0.66 to -0.67), and ankle plantarflexion (r= -0.53 to -0.60).Discussion Indices of coactivation, mirror movement, synergy, and overflow during single-joint lower limb tasks may quantify the type and degree of impairment in SMC. Preliminary concurrent validity between several of the indices of SMC and gross motor function was observed. Our findings established the feasibility of a new methodological approach that quantifies muscle activation patterns using electromyography paired with biofeedback during single-joint movement.